EMPLOYEE WORK SAFETY AND HEALTH TRAINING FOR GROUND HANDLING PERFORMANCE - Novi Indah Susanthi; Iqlima Puspa Seruni; Yunitha Ardiana Nur (Institut Transportasi dan Logistik Trisakti, 2017)
The objective of this research is to find out the influence of training variables of Occupational Health and Employee Performance. Data collection method used in this research was field research methods with a population of 30 respondents. Both methods of data analysis were also applied by using multiple linear regression analysis, validity test, reliability test, t-test, f-test, and coefficient determination. The issue discussed in this research is the lack of employee training in understanding the Occupational Safety Health in the warehouse. The results of analysis and discussion shows a proportional relationship between training of Occupational Safety and employee performance that the level of relationship variables belong to the strong category and Occupational Safety Health gives significant influence to employee performance variable.